Development of MOSHEE (E-Modul & E-Jobsheet) to Enhance Students' Learning Independence in the Network Measuring Instruments Subject - NOVA RACHMAWATI; Ekohariadi Ekohariadi; Ratna Suhartini; Yessy Yessy; Achmad Imam Agung (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
Learning success is influenced by several factors, one of them is learning media. The shift from teacher-centered learning to student-centered learning requires teachers to act as facilitators in developing media that support learner independence. This study aims to develop MOSHEE (E-module and E-jobsheet) based on Book Creator and to examine its feasibility and effectiveness in improving students’ learning independence in the Network Measurement Tools subject for Grade X TKJ students at SMKN Prigen, Pasuruan. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The trial was conducted through a quasi-experimental design involving two groups, namely the experimental class and the control class. The results showed that the media validity level reached 93.75%, categorized as highly valid, while the material validity reached 95.07%, categorized as highly feasible. Students’ learning independence reached 90%, indicating that MOSHEE was able to improve students’ learning independence. In addition, a reliability test of the learning independence questionnaire instrument was conducted, resulting in a reliability value of 0.801, which is included in the high category. Based on these findings, MOSHEE is considered feasible as a learning medium and effective in improving students’ learning independence.